2015
DOI: 10.4166/kjg.2015.65.6.366
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Disseminated Intra-abdominal Gastrointestinal Stromal Tumor Managed with Low Dose Imatinib

Abstract: Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the gastrointestinal tract. Imatinib mesylate is recommended as adjuvant therapy for GIST after surgical resection. However, drug-related adverse events are common. A 74-year-old female with metastatic GIST who was managed with imatinib experienced severe adverse events, including skin rashes, tremor, and alopecia, etc. The imatinib dose was reduced and the size of the metastatic GIST continued to decrease and adverse events showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Topical and systemic corticosteroids have been found to be effective against imatinib-induced skin reactions [10] . Low-dose imatinib was sufficiently effective in our two reported cases as well as in past case reports [9] . However, it is still unknown whether reduced-dose imatinib is also effective for GISTs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Topical and systemic corticosteroids have been found to be effective against imatinib-induced skin reactions [10] . Low-dose imatinib was sufficiently effective in our two reported cases as well as in past case reports [9] . However, it is still unknown whether reduced-dose imatinib is also effective for GISTs.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, we reduced the dose of imatinib to control adverse events. A previous case report showed that reducing imatinib to 200 mg/day allowed patients with metastatic GIST suffering from severe adverse events, such as skin rash, tremor, and alopecia, to continue treatment with tolerable side effects (rash) [9] . In case 2, we combined systemic steroids for skin rash.…”
Section: Discussionmentioning
confidence: 99%
“…13 Thus, in Asia, lowdose continuous adjuvant imatinib should be recommended for intolerable patients, as supported by relevant research. 32,33 As the recommended dose cannot be tolerated for some Asian patients, finding the optimal treatment duration could be more important than increasing the dose of imatinib for such patients. Therefore, seeking the appropriate adjuvant duration for imatinib might be the key point of studies at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…Among 855 patients, 17.7% (n = 151) of the patients discontinued adjuvant imatinib for intolerance or severe side effects within 1 year, which was more than that in the RCT including Westerners only 13 . Thus, in Asia, low‐dose continuous adjuvant imatinib should be recommended for intolerable patients, as supported by relevant research 32,33 . As the recommended dose cannot be tolerated for some Asian patients, finding the optimal treatment duration could be more important than increasing the dose of imatinib for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…The gradual decrease reduced the size of the metastatic GIST and notably mitigated the adverse events. [15] Meanwhile, Faber et al [16] reported that lower dose IM can be effective in patients with chronic myeloid leukemia. Considering the high inter-individual pharmacokinetic variability of IM, these results suggest that a more individualized treatment is more appropriate than methods with fixed dosage of IM.…”
Section: Discussionmentioning
confidence: 99%